A modified side‐to‐end lymphaticovenular anastomosis. Issue 2 (14th September 2012) - Yamamoto, Takumi; Yoshimatsu, Hidehiko; Narushima, Mitsunaga; Seki, Yukio; Yamamoto, Nana; Shim, Timothy Weng Hoh; Koshima, Isao
Abstract Background: Lymphaticovenular anastomosis (LVA) is a useful treatment for compression‐refractory lymphedema with its effectiveness and minimal invasiveness. However, LVA requires supermicrosurgery, where lymphatic vessels with a diameter of 0.5 mm or smaller are anastomosed using 11‐0 or 12‐0 suture. To make LVA easier and safer, we adopted a modified side‐to‐end (S‐E) anastomosis in LVA surgery. Methods: We performed modified S‐E LVAs in 14 limbs of female patients with lower extremity lymphedema (LEL). In modified S‐E LVA, lateral windows with a length of 1.0 mm or longer were created on a lymphatic vessel and a vein, respectively, and side‐to‐side (S‐S) anastomosis was established with 10‐0 continuous suture. After completion of S‐S anastomosis, the vein distal to the anastomosis site was ligated to prevent venous backflow and subsequent thrombosis at the anastomosis site. Lymphedematous volume was evaluated preoperatively and at postoperative 6 months using LEL index. Results: All the 24 modified S‐E anastomoses could be completed without difficulty or revision for anastomosis, and showed good patency after completion of anastomosis. Postoperatively, LEL indices significantly decreased compared with preoperative LEL index (255.9 ± 14.1 vs. 274.9 ± 22.2, P < 0.001). Conclusions: Modified S‐E LVA can efficaciously divert lymph flows into venous circulation without performing supermicrosurgical anastomosis. © 2012 Wiley Periodicals, Inc., Microsurgery, 2013.